THE ROLE OF MURAQABAH IN DEVELOPING PEDAGOGICAL COMPETENCE AMONG ISLAMIC HIGHER EDUCATION LECTURERS - Usman, Usman; Usman, A’zhami Alim; Azizah, Faras Puji (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
The academic competence of lecturers is crucial for student success and the overall quality of education. This study aims to explore how the practice of muraqabah can enhance the pedagogical competence of lecturers, specifically those at Islamic universities in Sumatera, Indonesia. A qualitative, phenomenological approach was employed, using semi-structured and open-ended interviews to collect data from four participants. The interview transcripts were analyzed thematically. The findings revealed that muraqabah practice positively impacted lecturers, enhancing their attitudes, ethical values, empathy, and communication skills. It also promoted the development of professional academic qualities such as discipline, responsibility, tolerance, and compliance. Participants reported an improved ability to integrate moral values into their teaching practice, thereby contributing to their pedagogical competence. This study underscores the potential of murâqabah as a tool for developing pedagogical skills in higher education. Its findings imply that incorporating murâqabah practices into professional development programs for lecturers can strengthen their academic and pedagogical capabilities, ultimately benefiting the learning environment in higher education institutions in Sumatera, Indonesia.